2022
DOI: 10.3390/pharmaceutics14050982
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as a Natural Approach of Periodontal Adjunctive Treatment and Its Immunological Implications: A Narrative Review

Abstract: Scaling and root planing represent the gold standard in the treatment of periodontal disease, but these therapeutic methods cannot eliminate the remaining periodontopathogenic bacteria in cement, tubules, and periodontal soft tissue. Thus, a number of additional therapeutic means have been adopted, including local and systemic antibiotic therapy, as well as the use of photodynamic therapy techniques. Recently, special attention has been paid to potential phytotherapeutic means in the treatment of periodontal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Phytotherapeutic products, such as propolis [46] or turmeric [47], have also been addressed in the development of gels with subgingival application. Dave et al observed significant reductions in plaque index, bleeding on probing, probing depth and periodontal clinical attachment loss after turmeric gel [48].…”
Section: Gelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phytotherapeutic products, such as propolis [46] or turmeric [47], have also been addressed in the development of gels with subgingival application. Dave et al observed significant reductions in plaque index, bleeding on probing, probing depth and periodontal clinical attachment loss after turmeric gel [48].…”
Section: Gelsmentioning
confidence: 99%
“…The use of aPDT in adjunctive periodontal therapy can be amplified by applying a photosensitizing substance in the periodontal pocket and irradiating it with a light source (laser or LED) of a wavelength appropriate to the used substance [47,80]; cytotoxic reactive oxygen species are generated after exposure to light, with effects involving protein, cell membrane and bacterial organ damage [81] (Figure 2).…”
Section: Photodynamic Antibacterial Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin, as a main bioactive polyphenolic compound, is extracted from the curcuma longa (also known as tumeric) that is a plant belonging to the ginger family (Zingiberaceae), originated from India, and currently grown in Southeast Asia and China [ 15 ]. Curcuma has attracted broad attention from ancient times as it owns profound biochemical and biological activities, such as antiviral, antimicrobial, anti-inflammatory, and antioxidant activities [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%